Tindak Tutur Ilokusi Guru dalam Video Pembelajaran Bimbingan Belajar Daring Ruangguru - Ika Puput Oktavia Kumalasari; Suparno; Novi Eka Susilowati (Universitas Negeri Malang, 2021)
Abstract: This research is led by the current Covid-19 pandemic situation, which has resulted in changes in the education system so that it requires students to study at home or use an online learning system. Many students use the Ruangguru online tutoring application to help them understand the subject matter at school. This study aims to describe (1) the form of sentence, (2) types of illocutionary speech acts, (3) the function of illocutionary speech acts, and (4) teacher’s speech act strategies. The type of research in this research is descriptive qualitative. Data collection techniques in this study are listening techniques and note-taking techniques. Data analysis techniques in this study include data reduction, data presentation, and inference. The findings revealed 1) the sentence form are declarative, interrogative, and imperative, 2) the types of illocutionary speech acts are assertive, directive, expressive, and commissive, 3) the function of illocutionary speech acts is in the form of notifying, claiming, stating, speculating, concluding, showing, demanding, mentioning, opposing, ordering, inviting, asking, advising, congratulating, complaining, greeting, apologizing, and promising, 4) the speech act strategies found are direct speech act strategies and indirect. Keywords: illocutionary speech acts, learning video, tutoring, Ruangguru. Abstrak: Penelitian ini dilatarbelakangi oleh situasi pandemi Covid-19 saat ini yang mengakibatkan perubahan sistem pendidikan sehingga mengharuskan siswa untuk belajar di rumah atau menggunakan sistem pembelajaran daring. Siswa banyak menggunakan aplikasi bimbingan belajar daring Ruangguru untuk membantu memahami materi pelajaran di sekolah. Penelitian ini memiliki tujuan untuk menjabarkan (1) bentuk kalimat, (2) jenis tindak tutur ilokusi, (3) fungsi tindak tutur ilokusi, dan (4) strategi tindak tutur guru. Jenis penelitian dalam penelitian ini adalah deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini adalah teknik simak dan teknik catat. Teknik analisis data dalam penelitian ini meliputi reduksi data, penyajian data, dan penyimpulan. Hasil analisis data penelitian ini adalah 1) bentuk kalimat berupa deklaratif, interogatif, dan imperative, 2) jenis tindak tutur ilokusi berupa asertif, direktif, ekspresif, dan komisif, 3) fungsi tindak tutur ilokusi berupa fungsi memberitahukan, mengeklaim, menyatakan, berspekulasi, menyimpulkan, menunjukkan, menyebutkan, menentang, menyuruh, mengajak, meminta, menasihati, memuji, memberi selamat, mengeluh, menyapa, meminta maaf, dan berjanji. Keempat, Strategi tindak tutur berupa strategi tindak tutur langsung dan tidak langsung. Kata kunci: tindak tutur ilokusi, video pembelajaran, bimbingan belajar, Ruangguru